Pembentukan Karakter Religius Siswa Melalui Ekstrakurikuler Tahfidzul Qur’an Di Sekolah Dasar Muhammadiyah Plus Kota Probolinggo - Wildani Firdaus; Benny Prasetya; M. Chotibuddin (STIT Muhammadiyah Paciran Lamongan, 2023)
This research describes how the development of the religious character of students who take part in extracurricular tahfidzul qur'an activities at the elementary school level. In this activity also did not escape from the supporting and inhibiting factors. Through this research, there are problems that will be discussed, namely the moral degradation that is increasingly rampant. This chronic disease attacks many young generations today, therefore one way to prevent it is by bringing them closer to Islamic values ??through the Qur'an. The purpose of this study is to find out what impact is given from extracurricular activities tahfidzul qur'an, especially in the aspect of religiosity. To find out, the researcher used a qualitative study field research approach. The results of this study indicate that extracurricular tahfidzul qur'an is able to bring various positive impacts on students. In addition to cognitive development, children also show a change in their attitude or character for the better and begin to be able to control their relationship with God and each other.